Comparative Study of the Quality of Life and Coping Strategies in Oncology Patients - Meneguin, Silmara [UNESP]; Alves, Izadora Gama [UNESP]; Camargo, Heloiza Thais Felipe [UNESP]; Pollo, Camila Fernandes [UNESP]; Segalla, Amanda Vitoria Zorzi [UNESP]; de Oliveira, Cesar (MDPI, 2024)
Background: Despite the current data on morbidity and mortality, a growing number of patients with a diagnosis of cancer survive due to an early diagnosis and advances in treatment modalities. This study aimed to compare the quality of life and coping strategies in three groups of patients with cancer and identify associated clinical and sociodemographic characteristics. Methods: A comparative study was conducted with outpatients at a public hospital in the state of São Paulo, Brazil. The 300 participants were assigned to three groups: patients in palliative care (Group A), patients in post-treatment follow-up with no evidence of disease (Group B), and patients undergoing treatment for cancer (Group C). Data collection involved the use of the McGill Quality of Life Questionnaire and the Ways of Coping Questionnaire. No generic quality-of-life assessment tool was utilized, as it would not be able to appropriately evaluate the impact of the disease on the specific group of patients receiving palliative care. Results: Coping strategies were underused. Participants in the palliative care group had poorer quality of life, particularly in the psychological well-being and physical symptom domains. Age, currently undergoing treatment, and level of education were significantly associated with coping scores. Age, gender, income, and the absence of pharmacological pain control were independently associated with quality-of-life scores. Moreover, a positive association was found between coping and quality of life. Conclusion: Cancer patients in palliative care generally report a lower quality of life. However, male patients, those who did not rely on pharmacological pain control, and those with higher coping scores reported a better perception of their quality of life. This perception tended to decrease with age and income level. Patients currently undergoing treatment for the disease were more likely to use coping strategies. Patients with higher education and quality-of-life scores also had better coping scores. However, the use of coping strategies decreased with age.
Keywords: cancer; coping strategies; palliative care; quality of life